Teacher Professional Identity; A Study in the Linguistics Department of the School of Philology, Linguistics, and Literature of the University of Costa Rica - Cerdas Benavides, Cidalice (2012)
This article aims to analyze the professional identity of professors teaching in the Department of Linguistics at the School of Philology, Linguistics and Literature at the University of Costa Rica. In order to do so, it posits the question “How do professors providing lessons in Spanish Philology major define their identity?” Concerning the question, an analysis of the fundamental aspects of professional identity was executed taking into consideration: the conceptions of teaching and learning, strategies employed, as well as the related affective and motivational factors.